2019
DOI: 10.1021/acs.analchem.9b02845
|View full text |Cite
|
Sign up to set email alerts
|

Variable-Angle Nanoplasmonic Fluorescence Microscopy: An Axially Resolved Method for Tracking the Endocytic Pathway

Abstract: The study of endocytosis, which encompasses diverse mechanisms in biology, requires the utilization of high axial resolution to monitor molecular behavior on both the cell surface and interior of the cell. We have designed a novel axially resolved fluorescence microscopic technique, termed variable-angle nanoplasmonic fluorescence microscopy. The proof-of-principle of this approach is achieved by selectively following the events in the vicinity of a cell membrane or in a cell. We use a 30 nm Au-coated semitran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Recently, our group developed a novel imaging approach, termed as variable-angle nanoplasmonic fluorescence microscopy (VANFM), to selectively modulate the imaging depth with an improved axial resolution [81]. As SPCEM provides better axial confinement in the extremely close vicinity, we expect a higher imaging resolution in the axial direction with VANFM.…”
Section: Variable-angle Nanoplasmonic Fluorescence Microscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, our group developed a novel imaging approach, termed as variable-angle nanoplasmonic fluorescence microscopy (VANFM), to selectively modulate the imaging depth with an improved axial resolution [81]. As SPCEM provides better axial confinement in the extremely close vicinity, we expect a higher imaging resolution in the axial direction with VANFM.…”
Section: Variable-angle Nanoplasmonic Fluorescence Microscopymentioning
confidence: 99%
“…Previously, our group has provided a study to explore the cross-scale effect of SPCE and demonstrated its ability to study macro-scale cells [87]. Afterwards, we proposed the axial-resolved VANFM to release the axial restriction and applied it to observing the cellular activity [81].…”
Section: Monitoring Dynamics Of Receptor-mediated Endocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…As important spectral technologies, fluorescence-based techniques have been widely used in all kinds of analysis and detection, but insufficient sensitivity limits their further development. It has been shown that the radiation decay rate and the distribution of radiation energy of fluorophores can be changed when they are placed on a metal surface or a metal surface with nanostructures, which enables the increase of sensitivity. A new technique, namely, surface plasmon coupled emission (SPCE), in which directional and enhanced radiation is produced by the interaction between an excited fluorophore in the near-field (20–200 nm) of a continuous metallic surface and surface plasmons (SPs), has been developed and demonstrated to be useful in biochemical detection and imaging , due to its distance dependence and wavelength resolution.…”
mentioning
confidence: 99%
“…[34][35][36] Researchers, including our group, have utilized SPCE to study basal cellular membrane-related activities. [37][38][39][40][41] However, previous studies focused on investigating a single membrane domain, which is of no help for simultaneously determining the role of membrane domains in cellular functions. Thus, it is highly desirable to develop a microscopic technique capable of identifying and characterizing the basal and lateral membrane domains.…”
mentioning
confidence: 99%